Knowledge about menstruation with readiness to face menarche of elementary school students in the era of reproductive health education - Jessica Rotinsulu, Ria Angelina; Ati, Endang Puji (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Adolescence is a crucial period marked by various physical and psychological changes, including menarche, the first menstruation that often elicits mixed emotional responses. Adequate knowledge about menstruation can help mitigate feelings of fear, anxiety, and confusion, enhancing adolescents' readiness to face this natural developmental stage. This study aimed to investigate the correlation between the level of menstrual knowledge and the readiness to face menarche among female students. Method: A quantitative research design with an analytical survey and cross-sectional approach was applied. The research was conducted in April 2025 with 40 female students from grades IV to VI, selected via accidental sampling. Data collection used a structured questionnaire, and analysis involved univariate and bivariate statistics using the non-parametric Kendall Tau correlation test. Results: The results showed that 47.5% of respondents had good menstrual knowledge, and 95% were considered ready to face menarche. However, statistical analysis yielded a p-value of 0.281 with a significance level of 0.045 (α = 0.05), indicating no significant correlation between menstrual knowledge and readiness to face menarche. Conclusion: Despite most respondents demonstrating good knowledge and readiness, no statistically significant correlation was found. This suggests that other factors may influence menarche readiness beyond menstrual knowledge alone. These findings underscore the need for broader support systems in adolescent reproductive health education